Implementation of automation tools for test analysis in the Radiotherapy Quality Assurance Programs - João Guilherme Rivera Santiago; Laura Furnari; Marcus Vinicius Saad de Paula Rodrigues; Victor Augusto Bertotti Ribeiro (Brazilian Journal of Radiation Sciences)
The increasing complexity of techniques used in radiotherapy demands a quality assurance program that evolves to ensure efficient quality control of equipment and associated devices. Many periodic tests rely on analyzing acquired images, typically compared to predefined standards to verify consistancy—checks that can often be automated. Automated analyses enable greater standardization, reduced subjectivity, improved accuracy, and shorter quality control times. To implement such tools, it is essential to assess factors such as accuracy, error detection sensitivity, adaptability to institution needs, and ease of access and use for those involved in quality control processes. This study evaluated two automation tool interfaces: the commercial SunCHECK Machine by Sun Nuclear® and a web application implementing modules from the open-source Pylinac library. Both interfaces were suitable to the quality assurance program, using coherent methodologies to calculate key metrics outlined in reference documents. Each tool has unique features and specific considerations, highlighted throughout the study based on evaluating Picket Fence, Star Shot, Winston-Lutz tests, field analysis, and Cone Beam Computed Tomography image quality. The findings highlight the importance of conducting studies during the implementation phase of such tools to understand the algorithms used and establish appropriate usage and control measures for routine practice. Both interfaces proved capable of quantifying the relevant quantities based on the reference documents, providing more efficient and effective quality control.